Block Model of Laterite Nickel Reserve in the Sorowako Village Research Area, South Sulawesi Province - Yunita Nurjayanty; Djamaluddin Djamaluddin; Agus Ardianto Budiman (CV Insight Publisher, 2022)
The manufacture of laterite nickel deposit model blocks is one of the stages after exploration activities are carried out in an area that shows potential resources that are feasible to be exploited. The purpose of this study was to determine the tonnage value of an estimated resource of saprolite and limonite ore deposits in the drilling area. The research method is the implementation of fieldwork, which includes a survey of the area to be drilled, tools and materials used in drilling production, and determining the stages in making model blocks. The data used in this study are data from analysis of nickel content, data on the total depth of drill points, lithology data of laterite nickel profiles, and data on coordinates and elevation of drill points. In research conducted in the concession area of ​​the research area with a number of drill points of as many as 275 points and a drill spacing of 25 meters and 50 meters, the number of resources that have been calculated in the form of a 3D block model and a cross-sectional vertical correlation where in the limonite layer the volume value is obtained. of 757,031 m3 with an average Ni content: 0.84%, while the saprolite layer obtained a volume value of 210,781 m3 with an average Ni content: 1.80%. The conclusion obtained is that the tonnage value for the limonite layer is 1,211,250 tons, and for the saprolite layer the tonnage value is 400,484 tons.